2008
DOI: 10.1088/0967-3334/29/6/s27
|View full text |Cite
|
Sign up to set email alerts
|

Test of the method of differentiation between healthy and anomalous breast tissues using the open-ended dielectric probe covered by a dielectric film

Abstract: Dielectric properties of breast tissue obtained from 131 patients were investigated by an open-ended probe separated from the tissue by a dielectric film (plastic foil). The film decreases the measured capacitance, but the content of blood and body liquids has little effect on the measured quantity. We found that in cancerous tissue the electric capacity (related to the permittivity) measured at f > or = 10 MHz using the modified probe is higher than that in normal tissue. The dielectric assignment was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…It results in unrepeatable conditions of measurements making the diagnostic application of the dielectric method very difficult. To overcome these problems we propose blocking of the electrodes by using a non-conducting layer separating the tissue and the probe [6].…”
Section: Introductionmentioning
confidence: 99%
“…It results in unrepeatable conditions of measurements making the diagnostic application of the dielectric method very difficult. To overcome these problems we propose blocking of the electrodes by using a non-conducting layer separating the tissue and the probe [6].…”
Section: Introductionmentioning
confidence: 99%
“…The physics back- ground of the measurements and the tests carried out on reference substances and animal tissue have been described in earlier publications from physics journals [18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory testing has demonstrated that cancer tissue can be detected both on the surface of a specimen as well as underneath a 1-2 mm layer of healthy breast tissue [18,19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations